Revascularization strategies in Non-ST segment elevation myocardial infarction: the clash continues - Zuccarelli, Vittorio; Giunti, Filippo; Chiarito, Mauro; Pivato, Carlo Andrea; Stefanini, Giulio Giuseppe (Frontiers in Cardiovascular Medicine, 2025)
For patients presenting with Non-ST-Elevation Myocardial Infarction (NSTEMI), the choice and timing of revascularization remain complex and debated. This decision is influenced by clinical factors such as hemodynamic stability, comorbidities and surgical risk profile, as well as anatomical considerations like coronary lesion complexity and feasibility of achieving complete revascularization. Randomized controlled trials directly comparing CABG and PCI in NSTEMI are limited, making evidence-based comparisons challenging. However, data suggest that while PCI is less invasive and offers rapid revascularization, CABG often achieves more comprehensive revascularization, particularly in high-risk patients with multivessel coronary artery disease, especially diabetic patients, or unprotected left main coronary artery disease. Over the last two decades, the adoption of CABG in NSTEMI has declined, driven by the advantages of PCI's minimally invasive nature and advancements in stent technology. Nevertheless, CABG remains essential in cases of complex coronary anatomy or where PCI fails to achieve adequate revascularization. Available outcome data indicate that CABG offers significant long-term benefits, including lower rates of myocardial infarction and repeat revascularization, although it is associated with an increased short-term risk of stroke, and surgical related bleeding. This review critically analyzes clinical scenarios in NSTEMI, examining the risks and benefits of CABG and PCI. It highlights the importance of individualized decision-making, guided by multidisciplinary Heart Teams, to balance procedural risks and long-term outcomes for optimal patient care